Professional Quality of Life and Occupational Stress in Healthcare Professionals During the COVID-19 Pandemic in Greece - Dimitra Latsou; Fevronia-Maria Bolosi; Lorena Androutsou; Mary Geitona (SAGE Publishing, 2022)
Background: Health professionals (HPs) coping with the coronavirus pandemic are at risk of working under stressful conditions impacting their professional well-being. The aim of this paper was to explore HP's professional quality of life and occupational stress during the COVID-19 pandemic in Greece. Method: A cross-sectional study was conducted (from October to December 2020) in a COVID-19 reference hospital, one of the biggest in Attica. The method of convenience sampling has been used. Data collection was carried out through an anonymous, self-administered questionnaire including, apart from HPs' demographic and occupational characteristics, Professional Quality of Life Scale (ProQoL) and Job Stress Measure. A total of 250 questionnaires were distributed to physicians and nurses. One hundred eighty-six questionnaires were fully completed (response rate = 78.8%). The analysis was based on descriptive and inductive statistics, using SPSS v25. Results: Participants' mean age was 41.5 ± 10.4 years; 75.3% were women and 62.4% was nursing staff. ProQoL analysis showed that the majority had moderate compassion satisfaction (74.2%) and burnout (78.5%), while 48.8% had moderate level of secondary post-traumatic stress. The mean value of occupational stress was estimated at 2.76, showing a moderate level of stress. HPs' demographic and occupational characteristics seemed to affect both work stress and ProQoL ( P  ⩽ .05). Occupational stress was positively correlated with both burnout ( r  = 0.461, P  = .001) and secondary post-traumatic stress ( r  = 0.596, P  = .001), indicating that an increase in health professionals' stress at work corresponds to a simultaneous increase in ProQoL. Conclusions: HPs' professional quality of life and occupational stress seemed to be moderate during the COVID-19 pandemic in Greece. In order to achieve an improvement in HPs' overall professional well-being, priority should be given to the strengthening of the capacity of the healthcare system as well as to supporting HPs in both stress management and psychological resilience.